Optimal rate and schedule of nitrogen fertilizer application for enhanced yield and nitrogen use efficiency in dry-seeded rice in north-western India. Issue 2 (28th January 2018) - Thind, Harmit Singh; Singh, Yadvinder-; Sharma, Sandeep; Goyal, Deepak; Singh, Varinderpal-; Singh, Bijay-
ABSTRACT: Dry direct-seeded aerobic rice (DSR) is an emerging attractive alternative to traditional puddled transplanted rice (PTR) production system for reducing labour and irrigation water requirements in the Indo-Gangetic plains (IGP) of India. The fertilizer N requirement of DSR grown with alternate wetting and drying water management may differ from that of PTR grown under continuous flooding due to differences in N dynamics in the soil/water system and crop growth patterns. Limited studies have been conducted on optimizing N management and application schedule for enhanced N use efficiency in DSR. Therefore, field experiments were conducted over 3 years in NW India to evaluate the effects of N rate and timing of its application on crop performance and N use efficiency. Interaction effects of four N rates (0, 120, 150, and 180 kg ha −1 ) as urea and four schedules of N application on yield and N use efficiency were evaluated in DSR. The N schedules included N application in three equal split doses (0, 35 and 63, and 14, 35 and 63 days after sowing, DAS) and four equal split doses (0, 28, 49 and 70; 14, 28, 49 and 70 DAS). There was no significant interaction between N rate and schedules on grain yield. Significant response to fertilizer N was observed at 120 kg N ha −1 and economic optimum dose for three equal split doses and skipping N at sowing was 130 kg N ha −1 . Highest mean grain yield of 6.60 t ha −1 was obtained when N was applied in three equal split doses at 14, 35 and 63 DAS which was about 8.5% higher compared with N applied in four equal split doses at 14, 28, 49 and 70 DAS. Under the best N application schedule, agronomic N use efficiency (26 kg grain kg −1 ), recovery efficiency (49%) and physiological efficiency (53 kg kg −1 ) were comparable to the values reported in Asia for PTR. Results from our study will help to achieve high yields and N use efficiency in DSR to replace resource intensive PTR.